Assessment of the operating mode of BelAZ dump trucks by the criterion of the efficiency of use of the resource of their internal combustion engine - Maslyukov S.P. (Горное оборудование и электромеханика)
In this article, the author presents an approach to assessing the operating mode of heavy-duty BelAZ-75306 quarry dump trucks at domestic coal mining enterprises, which allows increasing the service life of internal combustion engines of these machines without attracting significant capital investments. The difference between this approach and the generally accepted ones is the application of the criterion of efficiency of the use of the internal combustion engine resource of BelAZ dump trucks, determined by the ratio of the actual internal combustion engine resource before or between major repairs to its maximum value achieved by the same type of engines in comparable mining, geological and climatic operating conditions. A matrix of the skill level of dump truck drivers and the quality of the road surface has been constructed, which can be used to predict the range of specific diesel fuel consumption in the 95th percentile. It is substantiated that depending on the combination of driver qualification levels and road surface quality, four operating modes of dump trucks should be distinguished: gentle, actively forced, reactive forced, aggressive. A relationship was found between the efficiency of resource use of both new ICEs and those that have undergone the first and second major repairs from the distinguished operating modes of dump trucks. The difference in the efficiency of using the internal combustion engine resource was established when changing the operating mode of a dump truck, relative to the gentle mode.